Answer: see below
<u>Step-by-step explanation:</u>
The vertex form of a quadratic equation is: y = a(x - h)² + k where
- "a" is the vertical stretch (positive = min [U], negative = max [∩])
- (h, k) is the vertex
- Axis of Symmetry is always: x = h
- Domain is always: x = All Real Numbers
- Range is y ≥ k when "a" is positive or y ≤ k when "a" is negative
a) y = 2(x - 2)² + 5
↓ ↓ ↓
a= + h= 2 k= 5
Vertex: (h, k) = (2, 5)
Axis of Symmetry: x = h → x = 2
Max/Min: "a" is positive → minimum
Domain: x = All Real Numbers
Range: y ≥ k → y ≥ 5
b) y = -(x - 1)² + 2
↓ ↓ ↓
a= - h= 1 k= 2
Vertex: (h, k) = (1, 2)
Axis of Symmetry: x = h → x = 1
Max/Min: "a" is negative → maximum
Domain: x = All Real Numbers
Range: y ≤ k → y ≤ 2
c) y = -(x + 4)² + 0
↓ ↓ ↓
a= - h= -4 k= 0
Vertex: (h, k) = (-4, 0)
Axis of Symmetry: x = h → x = -4
Max/Min: "a" is negative → maximum
Domain: x = All Real Numbers
Range: y ≤ k → y ≤ 0
d) y = 1/3(x + 2)² - 1
↓ ↓ ↓
a= + h= -2 k= -1
Vertex: (h, k) = (-2, -1)
Axis of Symmetry: x = h → x = -2
Max/Min: "a" is positive → minimum
Domain: x = All Real Numbers
Range: y ≥ k → y ≥ -2
Answer:
Step-by-step explanation:
1 In general, given a{x}^{2}+bx+cax
2
+bx+c, the factored form is:
a(x-\frac{-b+\sqrt{{b}^{2}-4ac}}{2a})(x-\frac{-b-\sqrt{{b}^{2}-4ac}}{2a
2a
−b+√
b
2
−4ac
)(x−
2a
−b−√
b
2
−4ac
)
2 In this case, a=1a=1, b=-2b=−2 and c=-2c=−2.
(x-\frac{2+\sqrt{{(-2)}^{2}-4\times -2}}{2})(x-\frac{2-\sqrt{{(-2)}^{2}-4\times -2}}{2})(x−
2
2+√
(−2)
2
−4×−2
)(x−
2
2−√
(−2)
2
−4×−2
)
3 Simplify.
(x-\frac{2+2\sqrt{3}}{2})(x-\frac{2-2\sqrt{3}}{2})(x−
2
2+2√
3
)(x−
2
2−2√
3
)
4 Factor out the common term 22.
(x-\frac{2(1+\sqrt{3})}{2})(x-\frac{2-2\sqrt{3}}{2})(x−
2
2(1+√
3
)
)(x−
2
2−2√
3
)
5 Cancel 22.
(x-(1+\sqrt{3}))(x-\frac{2-2\sqrt{3}}{2})(x−(1+√
3
))(x−
2
2−2√
3
)
6 Simplify brackets.
(x-1-\sqrt{3})(x-\frac{2-2\sqrt{3}}{2})(x−1−√
3
)(x−
2
2−2√
3
)
7 Factor out the common term 22.
(x-1-\sqrt{3})(x-\frac{2(1-\sqrt{3})}{2})(x−1−√
3
)(x−
2
2(1−√
3
)
)
8 Cancel 22.
(x-1-\sqrt{3})(x-(1-\sqrt{3}))(x−1−√
3
)(x−(1−√
3
))
9 Simplify brackets.
(x-1-\sqrt{3})(x-1+\sqrt{3})(x−1−√
3
)(x−1+√
3
)
Answer:
Step-by-step explanation:
-3y = -2x + 5
y = 2/3x - 5/3
y + 1 = 2/3(x - 2)
y + 3/3 = 2/3x - 4/3
y = 2/3x - 7/3
Answer:
her ist answer
Step-by-step explanation:
plz rate and like my answer